2020
DOI: 10.2298/botserb2002121h
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas-based genome editing to improve abiotic stress tolerance in plants

Abstract: Climate change is affecting agriculture in a number of ways, such as changing water distribution, daily temperatures and salinity patterns. In this regard, plant breeding innovations and genetic engineering approaches to improve abiotic stress tolerance are necessary to avoid a decline in crop yields caused by climate change during the 21st century. In the last few years, genome editing using the CRISPR/Cas system has attracted attention as a powerful tool that can generate hereditary mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…The intricacy and redundancy of the plant genome make it likely that changing one mutation won't be enough to affect cellular activities. Through the integration of numerous promoter-designed gRNA cassettes into a single vector system, The CRISPR/Cas9 system may modify multiple genes (Hyun, 2020;Abdallah et al, 2022). To assure construct activity, these 5 constructs must undergo experimental validation.…”
Section: Construct Design and Transformation Construct Design And Tra...mentioning
confidence: 99%
“…The intricacy and redundancy of the plant genome make it likely that changing one mutation won't be enough to affect cellular activities. Through the integration of numerous promoter-designed gRNA cassettes into a single vector system, The CRISPR/Cas9 system may modify multiple genes (Hyun, 2020;Abdallah et al, 2022). To assure construct activity, these 5 constructs must undergo experimental validation.…”
Section: Construct Design and Transformation Construct Design And Tra...mentioning
confidence: 99%
“…Rice mutant SAPK2 was considerably more sensitive to oxidative and drought conditions than wild type implying that SAPK2 is required for drought tolerance in rice and thus could be a promising gene of interest for further crop improvement [ 39 ]. Comparable to this, in maize, ARGOS8-v2 and ARGOS8-v1 had transcriptional levels that were dramatically higher compared to the wild type, and the ARGOS8 variation had significantly enhanced grain output during drought conditions with minimal yield reduction during normal growing conditions [ 40 ]. Scientists subsequently confirmed that ARGOS8 variations created by CRISPR/Cas9 produced more grain in the fields even during dry season.…”
Section: Crispr and Crop Productivity In Drought Resilient Cropsmentioning
confidence: 99%
“…Subsequently, these breaks are repaired by endogenic cell mending, leading to the expansion of novel mutations [ 29 , 30 ]. The CRISPR–Cas system has been professionally used for achieving resistance to multiple stresses, including heavy metals, salinity, drought, and submergence [ 31 , 32 ]. The present review emphases on the application of the CRISPR–Cas9 system to achieve drought tolerance in plants and discusses the potential of this technology in the expansion of drought-tolerant plant varieties.…”
Section: Molecular Mechanisms Underlying Plant Drought Tolerancementioning
confidence: 99%